Layer upon Layer: Mao-Era History and the Construction of China's Agricultural Heritage. Issue 3 (1st September 2019) - Schmalzer, Sigrid
Abstract: Chinese scientists and scholars are actively engaged in a transnational movement to preserve agricultural heritage . The author places this current phenomenon in historical context to explore the changing epistemological assumptions undergirding the agricultural heritage concept. She shows that the discourse on agricultural heritage in China today quietly draws on Mao-era projects; however, the earlier focus on peasant experience has given way to an emphasis on culture more resonant with global currents today. The article further traces the influence of systems theory and ecoagricultural engineering, along with the transformations accompanying the rise of the market economy and tourism industry. Focusing on the celebrated terraces of Wangjinzhuang as a site of agricultural heritage preservation, the author argues that today's cultural systems paradigm captures the collective character of knowledge better than the experience paradigm did, but that it has simultaneously produced an artificial binary between tradition and modernity that flattens history and especially obscures Mao-era contributions to knowledge production. She proposes that scholars adopt a critical historical approach to recognize the significance of the Mao era in the construction of both agricultural knowledge and the agricultural heritage paradigm, while resisting efforts to co-opt that history in the service of state power.